Bulacan Capitol Plaza - Danao, Madonna (Sanyata; Vol 1 (2024): Sanyata: Journal of Creative Works of the Philippine Built Environment, 2025)
The revitalized Bulacan Capitol Plaza offers a more welcoming, accessible, and sustainable public space for residents and visitors to enjoy.